Postharvest Physiology and Physiological Disorders of Persimmon Fruit - Fariborz Habibi; Ali Sarkhosh; Steven A. Sargent (EDIS)
Persimmons are classified under the genus Diospyros within the family Ebenaceae. This genus includes different species such as the most popular, D. kaki (Japanese persimmon); D. virginiana (common persimmon); and D. lotus (date-plum, also known as Caucasian or lilac persimmon). Persimmons are temperate deciduous trees or evergreen subtropical or tropical trees. Their fruit exhibit a double sigmoidal growth curve, whether seeded or parthenocarpic. Persimmon fruit are widely appreciated for their unique flavor, high nutritional value, and bioactive compound content. Persimmons are climacteric, leading to significant postharvest challenges. This publication discusses the postharvest physiology and physiological disorders of persimmon fruit, focusing on how postharvest factors affect fruit quality and shelf life.